Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.050
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Culture and Perceived Organizational Support on Employee Engagement

Abstract: This research aims to explain the impact of organizational culture and perceived organizational support on employee engagement. This research uses a quantitative approach. Data collection is conducted through a survey of 131 employees of PT. Terminal Petikemas Surabaya. Sampling techniues in this study used incidental sampling. Analysis of research data was conducted using multiple linear regression analysis techniques. The results showed that organizational culture and Perceived Organizational Support both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Aspects of organizational culture that emphasize integrity, professionalism, praiseworthy, and adequate recognition for human resources can impact employee engagement. The analysis results follow previous research studies, which show that work culture positively influences work engagement (Bija, 2020 ; Nurcholis and Budi, 2019 ); organizational culture significantly positively influences work engagement (Siddique, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Aspects of organizational culture that emphasize integrity, professionalism, praiseworthy, and adequate recognition for human resources can impact employee engagement. The analysis results follow previous research studies, which show that work culture positively influences work engagement (Bija, 2020 ; Nurcholis and Budi, 2019 ); organizational culture significantly positively influences work engagement (Siddique, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…In another empirical study (Bija, 2020 ), work culture also mediates the influence of leadership on work engagement. Nurcholis and Budi ( 2019 ) show that both work culture and perceived organizational support can increase employee engagement, either partially or simultaneously. An empirical study at nine government bank branch offices in Malang, Indonesia (Hasan et al, 2020 ) showed that organizational culture significantly and positively affects employee engagement.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…POS has been described in different forms in the literature (e.g., Huning et al, 2020; Nurcholis & Budi, 2020). Early research of Eisenberger et al (1986) described POS as employees in a global organization who believe that the organization values their efforts and looks after their welfare.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Those indicators affect employee engagement. It can be concluded that the implementation of organizational culture can consistently increase employee engagement (Budiono, Hamidah, & Yasin, 2019;Machmed Tun Ganyang, 2019;Nurcholis & Budi, 2020;Pepra-Mensah & Kyeremeh, 2018). A good organization can appreciate the contributions made by its employees.…”
Section: Resultsmentioning
confidence: 99%